VERBA AKTIVITAS MATA DALAM BAHASA MELAYU PONTIANAK - Juli, Reinada; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research is based on curiosity about eye activity verbs, especially in Pontianak Malay. The method used is descriptive method with a qualitative research form. Techniques for collecting data are observation techniques, interviews, note-taking, and documentary study techniques. Based on the results of data analysis, there were 31 data in the form of lingual units of eye activity verbs in Pontianak Malay consisting of 28 lingual units of eye activity verbs without using tools in Pontianak Malay and 3 lingual units of eye activity verbs using tools in Pontianak Malay. There are 25 lingual monomorphemic forms, 5 polymorphemic forms and 1 lingual unit phrases. The function of the lingual unit of eye activity verbs in Pontianak Malay based on the verbal function is 26, the number of adjective functions is 1 and the nominal function is 4. The meaning in the linguan unit of activity verbs eyes in Pontianak Malay based on 29 lexical meanings, 1 grammatical meanings and 1 contextual meanings. Supplementary forms for learning Indonesian based on eye activity verbs in Pontianak Malay are in the form of a descriptive text entitled Ways of the People of West Kalimantan Saying Eye Activities in Malay Pontianak.